Proposed Factory Area Location Alternative Selection Based on Multiple Criteria Decision Making Using Analytical Hierarchy Process Method (Case Studi PT. SKI) - Magdalena, Riana; Silalahi, Agustinus; Fendi, Su (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2018)
PT. SKI is a manufacturing company engaged in the production of hair and skin beauty products such as hair masks, shampoos, conditioners and others. Demand for beauty products that are increasing every day requires companies to produce more than inventory. One solution is to expand the production area in an increase large-scale production processes. However, the current production area which cannot optimally support this due to the absence of vacant land or expansion of the area that can be carried out. Based on the results of interviews with the head of the production section, the plan to move locations in several alternative places is the right solution for the company. In the specific task studied, the need for this location transfer will be related to multiple decision making taken by the company. One technique to identify these problems is using the Analytical Hierarchy Process or AHP method where this method is a simplification of complex problems that are not structured, strategic, and dynamic into their parts, and organize in a hierarchy. The level of importance of each criterion that supports decision support is relatively compared to other criteria by considering various considerations and then synthesizing to determine criteria that have high priority and play a role in influencing the results of the system. Based on the results, it is found that there are several criteria which plays an important role in the selection of factory location alternatives obtained in the mathematical equation. The first criterion namely Investment and Operations has a value of around 55.84% indicating that the first best alternative location in the sub criteria is land price, land area, expansion and employee salaries (UMR). Continued around 58.47% in the second general criteria, namely facilities with sub criteria of water, electricity, transportation and service which showed the best selection was in the first location alternative and 73.51% in the criteria for ease of licensing and transportation access at the first alternative location. By comparing the three data multiplication matrices and assessment criteria, it was found that a large comparison of the three general criteria had a total of 60.91% of the first alternatives being the priority of PT. SKI to choose the location of the new factory area, which is located in Padurenan, Gunung Sindur, Bogor, West Java.